Al-Tahlil Al-Taqabuliy baina Al-Lughah Al-Indunisiyyah wa Al-Lughah Al-‘Arabiyyah ‘ala Mustawa ‘Alamat Al-Tarqim fi Al-Kitabah - Ali Mudlofir; Khoirun Nisa Alwachidah; Muflihah Muflihah; Umi Hanifah (Rumah Jurnal IAIN Bukittinggi, 2021)
Scholars agree that similarities are one of the reasons for the ease with which students learn a second language, and differences are the reason for difficulties in learning it. This study discusses the contrastive analysis between Indonesian and Arabic regarding the chapter on punctuation marks and their benefits in learning writing skills for students of class X MAN 1 Pasuruan. The formulation of the problem in this study are: 1- What are the similarities and differences between Indonesian and Arabic regarding the punctuation chapter? 2- What are the benefits of the results of the contrastive analysis between Indonesian and Arabic regarding the chapter on punctuation marks and their benefits in learning writing skills for class X students of MAN 1 Pasuruan? The research method used by the researcher is descriptive qualitative method. Collecting data using observation method, interview method, test method, and documentation method. The research sample was all students of class X MIA II MAN 1 Pasuruan, totaling 34 students. The research results can be summarized as follows: There are similarities and differences in types and functions between Indonesian and Arabic punctuation marks, and there are benefits from applying the results of this analysis, it was found that the percentage of punctuation scores from the post-test reached 75.8%, and This result is greater than the pre-test result which was 58.9%.أكد العلماء أن التشابه سببا لسهولة الدارسين في تعلم اللغة الثانية الاختلاف سببا لوجود الصعوبات في تعلمها، هذا البحث يبحث عن التحليل التقابلي بين اللغة الإندونيسية واللغة العربية على مستوى علامات الترقيم والاستفادة منه في تعليم مهارة الكتابة لدى طلاب الصف العاشر بالمدرسة الثانوية الحكومية الأولى باسوروان. فتبحث الباحثة بقضايا البحث : 1- ما أوجه التشابه والاختلاف بين اللغة الإندونيسية واللغة العربية على مستوى علامات الترقيم؟ 2- كيف الاستفادة من نتائج التحليل التقابلي بين اللغة الإندونيسية واللغة العربية على مستوى علامات الترقيم لتعليم مهارة الكتابة لدى طلاب الصف العاشر بالمدرسة الثانوية الحكومية الأولى باسوروان؟. وطريقة البحث التي استخدمتها الباحثة هي الطريقة الكيفية الوصفية. ولجمع البيانات استخدمت الباحثة طريقة الملاحظة، و طريقة المقابلة، وطريقة الاختبار، وطريقة الوثائق، أما عينة البحث فهي جميع الطلاب في الفصل العاشر للعلوم الطبيعة الثاني بالمدرسة الثانوية الحكومية الأولى باسوروان وهم ۳٤ طالبا. وأما نتائج البحث فيمكن أن تتلخص: هناك أوجه التشابه والاختلاف النوعي والوظيفي بين علامات الترقيم الإندونيسية والعربية، ووجدت الاستفادة من هذه النتيجة التحليلية، أن معدل النتيجة المائوية عن علامات الترقيم من الاختبار البعدي بلغ 75.8%، وهذه النتيجة أكبر من نتيجة الاختبار القبلي الذي بلغ 58.9%.